The interrelationships of work-related factors, person-environment fit, and employee turnover intention - Chavis Ketkaew; Orasa Manglakakeeree; Phaninee Naruetharadhol (Cogent Business & Management, 2020)
Retaining human resources is essential for a company's competitiveness. Losing a high-capacity employee can hurt a company's performance. In this study, we investigate the inter-relationship among work-related factors, for instance, job stress, person-environment-fit, and quitting intention of employees in Thailand. Data were collected from 400 office workers in Bangkok, Thailand, utilizing structured questionnaires derived from the conceptual framework. The gathered data were analyzed using the structural equation modeling (SEM) approach. We found that work overload, role ambiguity, and role conflict, as mediated through job stress, would influence employee turnover intention. However, unlike the previous employee turnover intention model that factors were typically mediated through job stress, we found that higher responsibility and greater financial insecurity directly drive turnover intention (positively for financial insecurity but negatively for responsibility).
Keywords: 650; work-related factors; person-environment fit; person-organization fit; person supervisor fit; person-job fit; person group fit; overload; role ambiguity; role conflict; responsibility; financial insecurity; turnover intention